Faixa azul em Maceió: avaliação dos ganhos de velocidade dos ônibus por microssimulação do tráfego - Silva, Luiz Gustavo Oliveira da (2020)
The public transportation system, on bus, in Maceió, lives daily with various problems, operating poorly and consequently loses more users each year. Given the importance of this mode of transport for the full functioning of the city, some measures have been implemented in recent years in an attempt to bring some improvement to the system. A bus lane called “Faixa Azul” (a street lane dedicated to public transport) was the most important measure adopted on this context. First implemented in 2014 on the Fernandes Lima and Durval de Góes Monteiro avenues corridor (the city's main transport corridor) and a year later on the Comendador Leão and Dona Constança avenues, the aforementioned lane was mainly intended to speed up the operation of urban buses. which would certainly positively impact the system. After five years of its implementation, the question is: what were the impacts of the Faixa Azul on the operational speed of the public transport system in Maceió and what was the intensity of these impacts on the system?Certainly there were improvements in the system, but its amplitude was limited by the intrinsic characteristics of this priority measure. Therefore, this dissertation intends to evaluate the gains in the average operational speed of urban public transport by buses provided by the Faixa Azul of the Fernandes Lima / Durval de Góes Monteiro road corridor in the city of Maceió during the morning peak hour, this period of greater demand for the said road corridor. For this, it was necessary to carry out a simulation of urban traffic due to the absence of speed data or travel time for public transportation prior to the implementation of the priority measure. The results obtained reveal that there have been significant improvements in the average speed of operation and reduction in travel time, however, these improvements depend on constant actions of supervision and control of Faixa Azul. Therefore, it was found that, despite the significant improvements obtained with the Faixa Azul, the ease of invasion and the sharing of the lane in the various permitted situations generates several interferences from other vehicles that significantly impact its capacity. Thus, it is necessary to improve the mode of prioritization of public transport to obtain more constant results, investing, for example, in exclusive lanes for the bus system.